Comment moderation strategies in Canadian news media and their principles - Al-Rawi, Ahmed; Nicolai, Joseph (ALBAHITH ALALAMI, 2022)
This paper offers a critical examination of Canadian news guidelines and policies on user-generated content (UGC) posted on news-related comment sections and social media. The outline of how news-related UGC is moderated within Canadian news is achieved by looking at the online comment policies of major Canadian news organizations like . the CBC, CityNews (Halifax), CTV News, Glacier Media, Global News, The Globe and Mail, Narcity Media, Postmedia, QUB (Québecor), and Torstar.The policies highlight how Canadian news organizations have practical strategies to manage news-related UGC but also call upon positive and negative social principles, to flag ill practices, foster democracy, and fight against online hate speech and libel. The analysis shows how guidelines reflect many of the key principles highlighted in the literature review but make no reference to economic principles that are emphasized as important in academic and journalist concerns with moderating news-related UGC.